Inelastic Displacement Ratio Approach for Analyzing the Vertical Elasto-plastic Seismic Responses of Steel Beam Bridges - Jian YIN (Taiyuan Ligong Daxue xuebao, 2021)
The inelastic deformation of a steel beam bridge under vertical seismic actions would accumulate in the “downward” side, whereas in the “upward” side, the structure keeps elastic. An un-symmetric hysteretic model was established for the steel beam bridge subjected to vertical earthquake actions. By using 53 strong vertical earthquake records and a developed nonlinear dynamic analyzing code, the inelastic displacement demand of steel beam bridges under vertical seismic actions were computed. From the results, a higher equivalent vertical yield strength or a larger post-yield stiffness ratio would lead to a smaller inelastic seismic demand for steel beam bridges, as well as a decreased dispersion in the demand. Based on the numerical results, a formula for the inelastic displacement demand of steel beam bridges under vertical seismic actions was proposed. The proposed vertical inelastic displacement ratio approach was adopted to calculate the seismic responses of a steel truss beam bridge under vertical seismic excitations, the results obtained agree well with those given by the nonlinear response history analysis. For mid-span vertical displacement, the error of the result is less than 11%. For the quantity and the location of yield members, the results of the proposed approach are identical with those given by the response history analysis.